Biological characteristics of the bacteriophage LDT325 and its potential application against the plant pathogen Pseudomonas syringae - Liu, Li; Wang, Bing; Huang, Anqi; Zhang, Hua; Li, Yubao; Wang, Lei (Frontiers in Microbiology, 2024)
Bud blight disease caused by Pseudomonas syringae is a major bacterial disease of tea plants in China. Concerns regarding the emergence of bacterial resistance to conventional copper controls have indicated the need to devise new methods of disease biocontrol. Phage-based biocontrol may be a sustainable approach to combat bacterial pathogens. In this study, a P. syringae phage was isolated from soil samples. Based on morphological characteristics, bacteriophage vB_PsS_LDT325 belongs to the Siphoviridae family; it has an icosahedral head with a diameter of 53 ± 1 nm and nonretractable tails measuring 110 ± 1 nm. The latent period and burst size of the phage were 10 min and 17 plaque-forming units (PFU)/cell, respectively. Furthermore, an analysis of the biological traits showed that the optimal multiplicity of infection (MOI) of the phage was 0.01. When the temperature exceeded 60 ℃, the phage titer began to decrease. The phage exhibited tolerance to a wide range of pH (3-11) and maintained relatively stable pH tolerance. It showed a high tolerance to chloroform, but was sensitive to ultraviolet (UV) light. The effects of phage LDT325 in treating P. syringae infections in vivo were evaluated using a tea plant. Plants were inoculated with 2 × 10 7 colony-forming units (CFU)/mL P. syringae using the needle-prick method and air-dried. Subsequently, plants were inoculated with 2 × 10 7 PFU/mL LDT325 phage. Compared with control plants, the bacterial count was reduced by 1 log10/0.5 g after 4 days in potted tea plants inoculated with the phage. These results underscore the phage as a potential antibacterial agent for controlling P. syringae.